Socio-Political Dimensions of Identity and Conflict among Fulani Herdsmen in Nigeria - Wabuji, Adi Helen; Fayomi, Oluyemi O. (Journal of Law & Policy Review, 2025)
This study examines the socio-political and historical dimensions of the Fulani herdsmen phenomenon within Nigeria’s multiethnic society. Using a qualitative review of existing literature and secondary sources, this paper traces the historical evolution of Fulani pastoralism, with particular reference to the legacies of the 18th– to 19th–century Fulani jihad and its influence on contemporary identity formation and social relations. The findings indicate that Fulani herdsmen constitute a distinct socio-cultural and occupational group whose pastoral mobility, limited integration into formal state institutions, and historical marginalisation have contributed significantly to recurring conflicts with agrarian communities and broader security challenges in Nigeria. The study further shows that these conflicts are shaped not only by ethnic differences but also by environmental pressures, weak governance, and inadequate policy responses. The paper contributes to the discussion by reframing the Fulani herdsmen issue as a socio-political and historical phenomenon, rather than merely an ethnic or security problem. It underscores the need for historically informed, inclusive, and context-sensitive policy interventions to support conflict resolution and national integration.